The Effects Of Technology Acceptance Factors On Customer E-Loyalty and E-Satisfaction In Malaysia - Wong, Winnie Poh-Ming; Lo, May-Chiun; Ramayah, T. (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The rapid growth of Internet shopping has led to increasing interest in how to inspire customer e-loyalty and e-satisfaction in Malaysia. By using TAM and TRA as the theoretical base, this study aims to investigate the impact of perceived usefulness, perceived ease of use and perceived enjoyment on customer e-loyalty and e-satisfaction. SPSS and SmartPLS (M3) are used as the main analytical tool. 395 respondents participated in the study and empirical results indicated that perceived usefulness and perceived ease of use positively impacted customer e-loyalty and e-satisfaction. Several implications, limitations of the study, and recommendations for future research are outlined.